The impact of cognitive impairment and low muscle mass on all-cause mortality among older adults in China: An empirical analysis based on CLHLS cohort data - Huixia Cao; Jiefen Ou; Manzhi Gao; Yingying Zhong (PLoS ONE, 2026)
Background Cognitive impairment and low muscle mass are prevalent conditions in later life, and each has been independently associated with adverse health outcomes. Both conditions are heterogeneous and may arise from multiple underlying etiologies. However, evidence regarding their combined association with all-cause mortality remains limited, particularly among older adults in China. Therefore, this study aimed to investigate the independent and joint associations of cognitive impairment and low muscle mass with all-cause mortality using data from a large prospective cohort. Methods Data from the China Longitudinal Healthy Longevity Survey (CLHLS) collected between 2011 and 2018 were analyzed. Kaplan–Meier survival analyses and log-rank tests were conducted, and Cox proportional hazards models were applied to estimate hazard ratios (HRs) and corresponding 95% confidence intervals (CIs) for all-cause mortality. Subgroup and sensitivity analyses were additionally performed to evaluate the robustness of the findings. Results A total of 5,625 participants were included and classified into four groups: neither cognitive impairment (CI) nor low muscle mass (LMM) (CI − /LMM − , n = 1,698; 30.2%), low muscle mass only (CI − /LMM + , n = 2,795; 49.7%), cognitive impairment only (CI + /LMM − , n = 341; 6.1%), and both cognitive impairment and low muscle mass (CI + /LMM + , n = 791; 14.1%). Kaplan–Meier survival analyses and multivariable Cox proportional hazards models demonstrated that participants in the CI + /LMM+ group had the highest risk of all-cause mortality (p < 0.001). Compared with the CI − /LMM− group, the adjusted hazard ratios (HRs) were 1.29 (95% CI: 1.01–1.51) for the CI − /LMM+ group, 1.92 (95% CI: 1.50–2.45) for the CI + /LMM− group, and 2.54 (95% CI: 2.11–3.05) for the CI + /LMM+ group. Sensitivity analyses confirmed the robustness of the main findings, revealing a significant increasing trend in mortality risk across the four groups (trend p < 0.001). In subgroup analyses, the CI + /LMM+ group was significantly associated with an elevated risk of all-cause mortality among women and participants aged <80 years. Conclusions The coexistence of cognitive impairment and low muscle mass was associated with a substantially increased risk of all-cause mortality, particularly among women and individuals younger than 80 years. The concurrent presence of these conditions may help identify a subgroup of older adults at heightened risk of adverse outcomes, underscoring the importance of comprehensive geriatric assessment and enhanced clinical surveillance in aging populations.